Christian Theology and the Status of Animals - McLaughlin, R. author. aut Link
XII, 202 p.
Keywords: The author argues that there are conflicting traditions with regard to the question of what is the moral standing of animals according to Christianity. The dominant tradition maintains that animals are primarily resources but there are alternative strands of Christian thought that challenge this view.